2010
DOI: 10.1007/s10577-010-9127-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Xenopus tropicalis whole chromosome painting probes using laser microdissection and reconstruction of X. laevis tetraploid karyotype by Zoo-FISH

Abstract: Laser microdissection was used for the preparation of whole chromosome painting probes in Silurana (Xenopus) tropicalis. Subsequent cross-species fluorescence in situ hybridization (Zoo-FISH) on its tetraploid relative Xenopus laevis revealed persistence of chromosomal quartets even after 50-65 million years of separate evolution. Their arrangement is in a partial concordance with previous experiments based on similarity of a high-resolution replication banding pattern. Further support for an allotetraploid or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 32 publications
3
50
1
4
Order By: Relevance
“…Our results suggest that the ancestral bi-armed chromosome pair of homoeologous XLA15 and XLA18 may have been derived from the fusion of XTR9 and XTR10 in the ancestral species of X. tropicalis. The nine quartets identified in this study were not consistent with those determined by 5-bromo-2 0 -deoxyuridine/dT replication banding (Schmid and Steinlein, 1991) and cross-species chromosome hybridization with X. tropicalis-derived chromosome painting probes (Krylov et al, 2010). Krylov et al (2010) demonstrated that XLA11 þ 14 and XLA15 þ 18 were painted with XTR8 and XTR9 probes, respectively, and XLA14 and XLA18 were hybridized with XTR10 paint; however, XTR10 showed homology with XLA15 and XLA18 by comparative gene mapping in the present study.…”
Section: Discussioncontrasting
confidence: 83%
“…Our results suggest that the ancestral bi-armed chromosome pair of homoeologous XLA15 and XLA18 may have been derived from the fusion of XTR9 and XTR10 in the ancestral species of X. tropicalis. The nine quartets identified in this study were not consistent with those determined by 5-bromo-2 0 -deoxyuridine/dT replication banding (Schmid and Steinlein, 1991) and cross-species chromosome hybridization with X. tropicalis-derived chromosome painting probes (Krylov et al, 2010). Krylov et al (2010) demonstrated that XLA11 þ 14 and XLA15 þ 18 were painted with XTR8 and XTR9 probes, respectively, and XLA14 and XLA18 were hybridized with XTR10 paint; however, XTR10 showed homology with XLA15 and XLA18 by comparative gene mapping in the present study.…”
Section: Discussioncontrasting
confidence: 83%
“…In their pioneering cytogenetic work on the genus Xenopus , Janina Tymowska and co-workers (for references, see table 1 ) did not arrange the ordinarily stained chromosomes according to decreasing lengths, but established sophisticated standard karyotypes which were based on the relative sizes of short and long chromosome arms. Subsequently, these unconventional chromosome groupings were adopted by others in studies on chromosome banding [Sekiya and Nakagawa, 1983;Schmid et al, 1987;Schmid and Steinlein, 1991], chromosome painting [Krylov et al, 2010] and mapping of genes and repetitive DNA sequences [Courtet et al, 2001;Krylov et al, 2003Krylov et al, , 2007Tlapakova et al, 2005;Nanda et al, 2008;Uno et al, 2008Uno et al, , 2013. In the present study, this system is simplified and the chromosomes are arranged according to the new nomenclature of Xenopus chromosomes established by the Xenopus Gene Nomenclature Committee [Matsuda et al, this issue].…”
Section: Resultsmentioning
confidence: 99%
“…Following this very first trial, studies using Zoo-FISH with 8 probes obtained from X. tropicalis [Krylov et al, 2010], as well as FISH with 60 cDNA clones of X. laevis [Uno et al, 2013] were used to identify the exact tetraploid X. laevis karyotype. The 9 quartets identified by Uno et al [2013] are shown in figure 5 b.…”
Section: Reconstruction Of the Tetraploid Karyotype Of X Laevismentioning
confidence: 99%
“…It has been known for some time that X. tropicalis is a true diploid species, but X. laevis is an ancient allotetraploid (Tymowska 1991). A recent chromosome painting analysis provides confirmation of this hypothesis (Krylov et al 2010). Now that the X. laevis genome has been sequenced and annotated (xenbase.org), it is possible to find numerous cases of duplicate genes in this species.…”
Section: Comparison Of Sisrnas In X Tropicalis and X Laevismentioning
confidence: 99%